2020
DOI: 10.3390/polym12081806
|View full text |Cite
|
Sign up to set email alerts
|

Composite Fiber Networks Based on Polycaprolactone and Bioactive Glass-Ceramics for Tissue Engineering Applications

Abstract: In this work, composite fibers connected in three-dimensional porous scaffolds were fabricated by electrospinning, starting from polycaprolactone and inorganic powders synthesized by the sol-gel method. The aim was to obtain materials dedicated to the field of bone regeneration, with controllable properties of bioresorbability and bioactivity. The employed powders were nanometric and of a glass-ceramic type, a fact that constitutes the premise of a potential attachment to living tissue in the physiological env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Basically, the vibrational features were assigned to three main types of bonds: Si‒O, Ca‒O and Mg‒O [ 42 ], in correlation with the elemental ( Figure 5 ) and mineralogical ( Figure 7 ) details. Another specificity is related to the emergence of a supplementary large band in the powders spectra, namely the one centered at approximately 1420 cm −1 , which was attributed to the presence of residual nitrates [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Basically, the vibrational features were assigned to three main types of bonds: Si‒O, Ca‒O and Mg‒O [ 42 ], in correlation with the elemental ( Figure 5 ) and mineralogical ( Figure 7 ) details. Another specificity is related to the emergence of a supplementary large band in the powders spectra, namely the one centered at approximately 1420 cm −1 , which was attributed to the presence of residual nitrates [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, biodegradable polymers have been used in conjunction with bioactive glass as composite materials. Subsequently, polycaprolactone (which is a biocompatible and biodegradable polyester with high availability and suitability for manufacture) has been applied in bone scaffolds as reinforcement because of its physical, biological, and mechanical properties (Cannillo et al, 2010;Jinga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Here, polycaprolactone (PCL) takes the mechanical support role in the microstructure, and the collagen provides cell recognition signals which are crucial for cell behavior and development (Dong and Lv, 2016). The assessment of PCL/BG coatings on metallic substrates and the behavior under corrosive environments as well their mineralization effects have been subsequently reported (Yazdimamaghani et al, 2015;Jinga et al, 2020), although metallic implants are currently used in orthopedics, oral, and maxillofacial surgery, and they present serious disadvantages because of the release of metallic ions into the body. Therefore, to minimize this anodic dissolution, the assessment surface modification of these metallic substrates have been studied by techniques such as dip coating, deposition by spraying, and electrospinning, among others (Panahi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of PCL increased the viscosity of the polymer blend, making PGS suitable for electrospinning [ 16 , 18 ]. Taken together, this study shows that the blending of PGS and PCL was a useful strategy to complement their individual properties, such as mechanical properties and biological behavior, to increase the scaffold performance for tissue regeneration applications [ 19 ]. Various studies have reported on the fabrication of different inorganic nanoparticles such as bioactive glass [ 20 , 21 ], tricalcium phosphate [ 22 ] and hydroxyapatite [ 23 ] and their incorporation in natural or synthetic polymers such as the collagen, chitosan, polycaprolactone, poly lactic acid and polyhydroxyalkanoates.…”
Section: Introductionmentioning
confidence: 99%